The angular power spectrum measurement of the Galactic synchrotron emission in two fields of the TGSS survey - Choudhuri, S.; Bharadwaj, S.; Ali, S.; Roy, N.; Intema, Hubertus; Ghosh, A. (Oxford University Press, 2017)
Characterizing the diffuse Galactic synchrotron emission at arcminute angular scales is needed to reliably remove foregrounds in cosmological 21-cm measurements. The study of this emission is also interesting in its own right. Here, we quantify the fluctuations of the diffuse Galactic synchrotron emission using visibility data for two of the fields observed by the TIFR GMRT Sky Survey. We have used the 2D Tapered Gridded Estimator to estimate the angular power spectrum (Cℓ) from the visibilities. We find that the sky signal, after subtracting the point sources, is likely dominated by the diffuse Galactic synchrotron radiation across the angular multipole range 240 ≤ ℓ ≲ 500. We present a power-law fit, Cℓ=A×(1000l)β⁠, to the measured Cℓ over this ℓ range. We find that (A, β) have values (356 ± 109 mK2, 2.8 ± 0.3) and (54 ± 26 mK2, 2.2 ± 0.4) in the two fields. For the second field, however, there is indication of a significant residual point source contribution and for this field we interpret the measured Cℓ as an upper limit for the diffuse Galactic synchrotron emission. While in both fields the slopes are consistent with earlier measurements, the second field appears to have an amplitude that is considerably smaller compared to similar measurements in other parts of the sky.